Desain Cold Storage untuk Pembekuan Ikan Laut Menggunakan Perangkat Lunak Coolselector®2 - Selan, Rima Nindia (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
The process of cooling and freezing carried out on fish products is one of the preservation methods that apply a cooling machine in its operation. The refrigeration machine used applies a steam compression refrigeration system with R404A refrigerant as its working fluid. A design that is not following the standards can result in significant losses both in material and economic terms. Besides, the wrong model can also cause the performance of the engine to cool down. The purpose of this study is to design and analyze the performance of cold storage for freezing fish using Coolselector®2 software version 3.6.1. Performance analysis is based on superheating and subcooling temperature variations to determine its effect on the performance of the cooling engine. Changes for superheat temperatures carried out at the 8K, 9K, 10K, 11K and 12K levels while the subcooling temperature is considered constant at the 3K level. Variations were made at subcooling temperatures at the 3K, 4K, 5K, 6K and 7K levels with superheat temperatures considered consistent at the 5K level. The result of cold storage room design shows that the room has a cooling capacity of 14.54 kW. Analysis of the performance of the engine coolant design shows that the refrigeration machine has excellent performance. It will be proved by the higher subcooling and superheat temperatures, the COP also increase. The most top COP is at the 12K superheat temperature level of 2.045, while for the subcooling temperature at the 7K level of 3.144